Direct Sagittal Computed Tomography of Temporomandibular Joint - M.C. Pant; Ramesh Chandra; G.N. Agarwal; R. Pradhan; Manoj Chowdhry; P.K. Srivastava (Indian Journal of Plastic Surgery, 1990)
Direct sagittal scanning of TMJ with the help of computed tomography gives better information about the osseous alteration of mandibular condyle and temporal bone, joint space narrowing, meniscal configuration and range of movements. The use of 25 cm thick foam between the head rest and the patients's head was found to be simple, inexpensive and helpful in evaluating the various disorders of the temporo-mandibular joint.